Kolofon - Jepsen, Erik Thorlund (Biblioteksarbejde, 1999)
1. udgave, november 1999 ISBN 87-88524-63-9 © Forfatterne Redaktion: Hans Jørn Nielsen Marianne Lykke Nielsen Erik Thorlund Jepsen Marianne Hummelshøj Holm Ansvarshavende: Erik Thorlund Jepsen Layout: Bruno Kjær Billedkunst: Lone Frydendal